2017
DOI: 10.18632/oncotarget.17165
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3-KLF15 signaling ameliorates kidney injury induced by hypertension

Abstract: Renal fibrosis participates in the progression of hypertension-induced kidney injury. The effect of SIRT3, a member of the NAD+-dependent deacetylase family, in hypertensive nephropathy remains unclear. In this study, we found that SIRT3 was reduced after angiotensin II (AngII) treatment both in vivo and in vitro. Furthermore, SIRT3-knockout mice aggravated hypertension-induced renal dysfunction and renal fibrosis via chronic AngII infusion (2000 ng/kg per minute for 42 days). On the contrary, SIRT3-overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 50 publications
(45 reference statements)
0
27
0
Order By: Relevance
“…Therefore, we wondered whether miR‐101a ameliorated hypertensive kidney injury induced by AngII injection via targeting TGFβRI or not. Podocytes, highly specialized epithelial cells of glomerular filtration barrier, are important for maintaining glomerular filtration barrier and can generate various fibrosis factors under damage . Our data showed that restoring mir101a expression in mouse podocyte cells down‐regulated TGFβRI expression.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, we wondered whether miR‐101a ameliorated hypertensive kidney injury induced by AngII injection via targeting TGFβRI or not. Podocytes, highly specialized epithelial cells of glomerular filtration barrier, are important for maintaining glomerular filtration barrier and can generate various fibrosis factors under damage . Our data showed that restoring mir101a expression in mouse podocyte cells down‐regulated TGFβRI expression.…”
Section: Discussionmentioning
confidence: 67%
“…Renal fibrosis is one of the key pathways involved in hypertensive kidney injury . Histology images showed that renal fibrosis was attenuated in AngII+miR‐101a group compared to AngII and AngII+scramble groups (Figure A).…”
Section: Resultsmentioning
confidence: 97%
“…Microglia‐induced oxidative stress and neuron stem cell dysfunction can be attenuated by SIRT3 overexpression through mitochondrial apoptosis pathway, including the decreased mitochondrial permeability transition pore (mPTP) opening, reduced mitochondrial cytochrome C release to cytoplasm, declined Bax/Bcl‐2 ratio and inhibition of caspase‐3/9 activity . Moreover, HNK, as an activator of SIRT3, can also ameliorate kidney injury induced by hypertension via activating SIRT3/KLF15 signaling pathway . Besides, utilizing the Sirt3‐knockout mice and the overexpression of SIRT3 by lentivirus transfection, other studies showed that SIRT3 can protect against cardiac fibrosis by inhibiting myofibroblasts trans‐differentiation via regulation of the STAT3‐NFATc2 signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the observed mechanistic effects of SIRTs are so diverse, that it is difficult to narrowly classify them [69, 88, 91, 120]. Specific intracellular signaling molecules or pathways interacting functionally with or targeted directly by SIRTs include adenosine monophosphate-activated protein kinase (AMPK) – angiotensin-converting enzyme 2 (ACE2) signaling [69, 104], peroxisome proliferator-activated receptor (PPAR)γ [97], signal transducer and activator of transcription (STAT)3 [108], mammalian target of rapamycin (mTOR) [99, 102], nuclear factor erythroid 2-related factor 2 (Nrf2) [91, 117], Krüppel-like factor (KLF)15 [110], forkhead fox O1 (FOXO1) [66] and O3 (FOXO3) [67, 68], nuclear factor κB (NF-κB) [115], Notch1 [95], matrix metalloproteinase (MMP)-14 [92], manganese superoxide dismutase (MnSOD) [65, 87], and c-Jun [13]. …”
Section: Sirtuins and Tissue Fibrosismentioning
confidence: 99%